Physicochemical Properties of Granular and Gelatinized Lotus Rhizome Starch with Varied Proximate Compositions and Structural Characteristics - Xinyu Jiang; Yiting Gu; Lichao Zhang; Jinjian Sun; Jianan Yan; Ce Wang; Bin Lai; Haitao Wu (Foods, 2023)
As a traditional and popular dietary supplement, lotus rhizome starch (LRS) has health benefits for its many nutritional components and is especially suitable for teenagers and seniors. In this paper, the approximate composition, apparent amylose content (AAC), and structural characteristics of five LRS samples from different regions were investigated, and their correlations with the physicochemical properties of granular and gelatinized LRS were revealed. LRS exhibited rod-shaped and ellipsoidal starch granules, with AAC ranging from 26.6% to 31.7%. LRS-3, from Fuzhou, Jiangxi Province, exhibited a deeper hydrogel color and contained more ash, with 302.6 mg/kg iron, and it could reach the pasting temperature of 62.6 °C. In comparison, LRS-5, from Baoshan, Yunnan Province, exhibited smoother granule surface, less fragmentation, and higher AAC, resulting in better swelling power and freeze-thaw stability. The resistant starch contents of LRS-3 and LRS-5 were the lowest (15.3%) and highest (69.7%), respectively. The enzymatic digestion performance of LRS was positively correlated with ash content and short- and long-term ordered structures but negatively correlated with AAC. Furthermore, the color and network firmness of gelatinized LRS was negatively correlated with its ash content, and the retrograde trend and freeze-thaw stability were more closely correlated with AAC and structural characteristics. These results revealed the physicochemical properties of LRS from different regions and suggested their advantages in appropriate applications as a hydrogel matrix.